Airgap and safety: Metocean induced uncertainties affecting airgap assessments. (January 2019) - Haver, Sverre
Abstract: The safety aspect of the airgap question is discussed. Thereafter uncertainties related to airgap assessments will be discussed both for fixed platforms and semi-submersibles. The various sources are discussed and illustrated with examples. Results are discussed both for 10 −2 – annual probability scenario (ULS) and an ALS scenario (10 −4 annual probability). This because the most important difference between the two possible rule regimes for Norwegian Continental Shelf is the way ALS is introduced regarding airgap. Highlights: Discussion of rule regimes applied at the Norwegian Continental Shelf. Sources of uncertainties regarding determining airgap for fixed platforms. Uncertainties in predicting proper airgaps for semi-submersibles. Discussion of assumptions that must be made for a proper airgap assessment.